Intervenção federal para pôr fim ao grave comprometimento da ordem pública - Normanton, Ana Catharina Machado (2020)
This dissertation has as its object the analysis of the institute of federal intervention in Brazilian law, especially regarding the hypothesis of article 34, III of the Constitution of the Republic: federal intervention to put an end to serious impairment of public order. The research is inserted in the field of Constitutional Law, branch of Public Law focused on the organization of the State and safeguard of the fundamental rights. The perspective of the legal nature of the federal intervention decree, as well as the (im) possibility of judicial control of the measure are controversial in national and foreign doctrine. The controversy lies in the fact that federal intervention is an act conventionally identified as strictly political in nature and without jurisdictional control. The historical process of the emergence of federalism, the significance of the political autonomy of the federated members for the concept of federation, the reasons for the emergence of the federal intervention institute, as well as its history in the Brazilian context will be analyzed. The study of neoconstitutionalism and the role played by the judiciary in this phase of constitutional law will also be carried out. The work aims, through the analysis of the national and foreign specialized bibliography, as well as the jurisprudence and the study of comparative law, to define the concept, content, legal nature and limits of the political and discretionary power within the federal intervention institute to put serious damage to public order. The material object of the research analysis is fundamentally doctrinal and jurisprudential in the context of constitutional law. In methodological terms, the research uses the methodology of bibliographic and jurisprudential documentary analysis. The relevance of the theme is justified by the need for further study on such an intervention, due to its potential for abusive and authoritarian uses. Moreover, it appears that the academic debate on the subject is still incipient, which justifies further studies. Finally, this theme is still little explored in Brazilian doctrine under the intended focus, although it is of extraordinary practical importance and with profound theoretical developments